A Study on Teachers’ Competence in the Use of Instructional Media in Second Grade at Primary School - Yasmida, Siti; Lingga, Leny Julia (Raja Zulkarnain Education Foundation, 2025)
This study aims to analyze and describe teachers' ability to utilize learning media in Grade II of SD Negeri 003 Pangkalan Kerinci. The primary focus of this study is to determine the extent to which teachers can select, utilize, and integrate learning media that are suitable for the characteristics of early childhood learners at the elementary school level, particularly in the subject of Indonesian. The type of research used is descriptive qualitative. Data were collected through interviews, observations, and documentation involving several key informants, including the homeroom teacher of Grade II, the principal, and four students. To collect data on the ability of teachers to utilize learning media in Grade II of SD Negeri 003 Pangkalan Kerinci, non-test instruments were used, including observation sheets, interview guides, and document reviews of teaching modules, photographs, and individual monumental works. The data were analyzed qualitatively using a thematic approach. The results of this study indicate excellent abilities in selecting and utilizing learning media. Grade II teachers can choose media that are relevant to the goals and characteristics of their students and effectively integrate technology, such as PowerPoint and educational videos, into the learning process. Additionally, teachers' creativity and innovation in creating simple learning materials from readily available resources can increase students' interest and involvement, making the learning process more engaging and effective.